Biochemical and physiological responses of two grapevine rootstock genotypes to drought and salt treatments. (20th March 2014) - Meggio, F.; Prinsi, B.; Negri, A.S.; Simone Di Lorenzo, G.; Lucchini, G.; Pitacco, A.; Failla, O.; Scienza, A.; Cocucci, M.; Espen, L.
Abstract Background and Aims In the light of possible climate change, a crucial aspect for future Mediterranean Europe viticulture is the selection of new rootstocks exhibiting adaptability to drought and salt stress. In this context and considering recent literature, it is fundamental to increase our knowledge of the biochemical and physiological events that characterise stress responses in grapevine roots. In this study, leaf and root responses induced by water stress (WS) and sodium chloride (NaCl) exposure in a new selected genotype, named M4 (Vitis vinifera × V. berlandieri) × V. berlandieri cv. Resseguier n. 1), were compared with those of the commercial rootstock 101.14. Methods and Results The effect of progressive WS and NaCl exposure was studied under controlled environmental conditions on ungrafted plants grown in pots. Shoot growth, plant water status and leaf photosynthetic parameters were measured. The concentration of sugars, amino acids and total proteins, as well as the concentration of the more abundant ions, was determined in both leaf and root organs. The M4 genotype showed greater capacity to maintain photosynthetic activity, to accumulate osmotic compounds as well as to counteract Na and Cl accumulation. Conclusion The M4 genotype exhibited a greater capacity to tolerate both WS and exposure to an increasing concentration of Na and Cl, maintaining photosynthetic activity also under severe stress conditions. The root system appeared to play a central role in sustaining biochemical and physiological responses experienced under these adverse conditions. Significance of the Study This study showed that the tolerance to abiotic stress conditions, such as WS and NaCl exposure, depends on root integrity/functionality, confirming that these aspects must be considered in further selection programs.